Decision-Making Method Employed at Construction Planning Phase of Housing Development - Mohd Sofberi, Nurul Atiqah; Mohd Noh, Hamidun; Manap, Norpadzlihatun (International Journal of Sustainable Construction Engineering and Technology, 2021)
A correct decision made by decision-makers, at the planning phase, determines the success of a housing development project. Detailed decision supporting data is needed to provide specific guidance to private housing developers. The purpose of this paper is to define a decision-making method to be employed at the construction planning phase of a housing development project in Malaysia. Survey method is implemented using a questionnaire that was distributed to 67 private housing developers. The collected data was then analysed via Statistical Package for Social Sciences (SPSS) software. The outcomes of the analysis show that for Malaysian private housing developers, discussion and market/economic report are the most important methods that are applied while making a decision for a housing development project. Thus, this paper is supposed to guide private housing developers as well as governments in making decisions at the construction planning phase of housing development projects in Malaysia.